Pharmacologic Targets and Prototype Therapeutics in the Kallikrein-Kinin System: Bradykinin Receptor Agonists or Antagonists. (2006) - Sharma, J. N.; AL-Sherif, G.J.
Abstract : The kallikrein-kinin system (KKS) is a complex system produced in various organs. This system includes kininogen (precursor for kinin), kallikreins, and pharmacologically active bradykinin (BK), which is considered to be proinflammatory and/or cardioprotective. It is a proinflammatory polypeptide that is involved in many pathological conditions and can cause pain, inflammation, increased vascular permeability, vasodilation, contraction of various smooth muscles, as well as cell proliferation. On the other hand, it has been shown that BK has cardioprotective effects, as all components of KKS are located in the cardiac muscles. Numerous observations have indicated that decreased activity of this system may lead to cardiovascular diseases, such as hypertension, cardiac failure, and myocardial infarction. BK acts on two receptors, B1 and B2, which are linked physiologically through their natural stimuli and their common participation in a variety of inflammatory responses. Recently, numerous BK antagonists have been developed in order to treat several diseases that are due to excessive BK formation. Although BK has many beneficial effects, it has been recognized to have some undesirable effects that can be reversed with BK antagonists. In addition, products of this system have multiple interactions with other important metabolic pathways, such as the renin-angiotensin system.